First Report of Pseudaspidimerus trinotatus (Thunberg) Feeding on Rhopalosiphum maidis (Fitch) Infesting Zea mays L. - Anusree, S. S.; Anitha , N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Coccinellids are potential predators of various agricultural pests of economic significance and are widely exploited in biocontrol programmes. However among the described species of coccinellids, many of them remained unrecognized and researches were concentrated on a few coccinellids only. One such less exploited coccinellid, abundantly seen in many of the agricultural ecosystem is Pseudaspidimerus trinotatus (Thunberg). Earlier investigations on this beetle are limited. In this study, detailed illustrations and description notes were provided for P. trinotatus. Documentation of prey range of P. trinotatus was conducted. Rhopalosiphum maidis (Fitch) infesting Zea mays L. is reported as a new prey record for P. trinotatus. Further research on biological and ecological aspects of this beetle is needed to recognize its potential in regulating pest population in agro ecosystems.